Real-world use of dimehtyl fumarate in patients with plaque psoriasis: a Delphi-based expert consensus - Martina Burlando; Elena Campione; Aldo Cuccia; Giovanna Malara; Luigi Naldi; Francesca Prignano; Leonardo Zichichi (Dermatology Reports, 2022)
Dimethyl fumarate (DMF) was recently approved by the European Medicines Agency for systemic treatment of moderate-to-severe chronic plaque psoriasis. Appropriate management of DMF treatment is required to achieve optimal clinical benefits. Seven dermatology experts gathered online for three meetings to identify consensus on use of DMF in patient selection, drug dosage/titration, side effects management, and follow-up, with the aim to provide guidance on use of DMF for psoriasis in clinical dermatological practice based on literature data and expert opinion. Twenty statements were discussed and voted on using a facilitator-mediated modified Delphi methodology. Strong consensus was reached for all statements (agreement level of 100%). DMF treatment is characterized by dosage flexibility, sustained efficacy, high rates of drug survival, and low potential for drug–drug interactions. It can be used in a broad range of patients, including the elderly or those with comorbidities. Side effects (mainly gastrointestinal disorders, flushing, and lymphopenia) are frequently reported but are generally mild and transient and can be minimized by dosage adjustments and slow titration schedule. Hematologic monitoring throughout treatment course is required to reduce the risk of lymphopenia. This consensus document provides clinical dermatologists with answers on optimal use of DMF to treat psoriasis.